Ornament and efficiency: material performance and environmental logic of arabesque in Bayt Al-Razzaz - Abdelalim, Marwa; Essam, Bassel; Fahmy, Mohammad (Frontiers in Built Environment, 2025)
Islamic structure is distinguished by its integration of ornamentation, cultural symbolism, and environmental responsiveness. One of its most iconic features is the arabesque—an intricate, rhythmic design that embodies religious concepts and artistic sophistication. In historical Cairo, specifically during the Mamluk and Ottoman periods, arabesque flourished as a defining element of architectural identification. Simultaneously, conventional Islamic structure made use of passive layout techniques that enhanced indoor comfort and reduced energy intake. This research focuses on the housing heritage of ancient Cairo, with particular emphasis on Bayt Al-Razzaz, to discover how ornamentation and environmental design coexisted. The study examines the use of high thermal mass materials, including 40-cm limestone, which has a low U-value and efficiently regulates indoor temperature compared to ornamental substances such as 12-cm and 25-cm CMUs with lower thermal resistance. Key indoor environmental parameters—temperature stability, carbon dioxide concentration, and energy use—are analyzed to understand the overall performance of conventional strategies. Furthermore, the research reframes the arabesque as more than ornamental art, highlighting its function in conveying values of sustainability, identification, and cultural continuity. By revealing the synergy between form, function, and symbolism, this will enhance re-integrating passive design and ornamentation into contemporary sustainable architecture.